The Political Life of Two Scions of Zamorins Family of Kozhikode During Eighteenth Century - Praveen O. K & Vincy C. K
n the late 1970’s and 80’s, particularly after the appearance of Carlo Ginzburg’s ‘The Cheese and the Worms’ and Giovanni Levis’ ‘Inheriting Power’, micro history shook the ground of established historiographical paradigms and practices. Macro history and Micro history are both subfields of the ‘new history’ that emerged in the latter part of the twentieth century and as such, it purports, to focus upon the real people in history. When writing micro history, the author more concentrates upon a single individual or community and through study and analysis attempts to reach understanding of wider issues. It also means ‘the singularisation of history, which takes a resolute stance against ‘grand narratives’ singularisation of history, which takes a resolute stance against ‘grand narratives’.This paper intents to provide trajectories of the political life of two scions of Zamorins family of Kozhikode. They are valiya Ravivarma and Cheriya Ravivarma. A biographical scale is attempted here to portray the facets of social confusions and mired power equations in the changing political atmosphere of the time. The study follows tools of micro history. As such, it refrains from the traditional historical method of ‘grand historical narratives’. As such this is an intensive historical investigation of a well defined smaller unit. However, this can be distinguished from a simple case study in so far as micro history aspires to large questions in small places. By reducing the scale of observation the method tries to reveal the complicated function of individual relationship within each and every social setting and they stressed its difference from large norms. Kovilakam is the residence of the royal house hold. Zamorins ruling families are divided in to three kovilakams.They are Pandinjare Kovilakam ,puthiya kovilakam and kizhakke kovilakam Both Valiya(elder) Ravi Varma and cheriya(younger) Ravivarma belong to padinjare kovilakam. Present study tries to place the life of these scions on the context of a declining royal family facing unprecedented political and social threats. While studying the life of them we can understand not only the external factors but also the internal factors that were responsible for the decline. This study also helps to understand the social circumstances and chaos present while they were striving to locate themselves in the emerging scheme of power.